The genetic diversity and reproductive dynamics of sandalwood in Gunung Sewu (Java, Indonesia) in 2012-2019: designing conservation strategies in a continuous versus fragmented landrace - Yeni Ratnaningrum; Sapto Indrioko; Amellita Karrin; Aditya Kurniawan; ANGGI D.C. PUTRI (Society for Indonesian Biodiversity, 2021)
Abstract. Ratnaningrum YWN, Indrioko S, Karrin A, Kurniawan A, Putri ADC. 2021. The genetic diversity and reproductive dynamics of sandalwood in Gunung Sewu (Java, Indonesia) in 2012-2019: designing conservation strategies in a continuous versus fragmented landrace. Biodiversitas 22: 3219-3229. This research aimed to compare the dynamics of the genetic diversity, mating systems, and reproductive outputs of the most fragmented (Bejiharjo) and continuous (Bleberan) sandalwood landraces in Gunung Sewu in the flowering periods of 2012-2019. Among the different sandalwood landraces found in Gunung Sewu, Bejiharjo has the highest levels of santalol; unfortunately, this landrace also requires the most attention because of heavy habitat fragmentation resulting from overexploitation, urbanization, and cave-tourism activities. Compared with Bejiharjo, Bleberan demonstrated a wider genetic base and greater outcrossing. Mature and flowering individuals in Bejiharjo decreased from 2012 to 2019 as fragmentation increased, particularly in 2019, during which extreme individual reduction due to illegal logging and land conversion was noted. Recent years consisted of more-clonalized stands, as indicated by the finding of fewer distinct genotypes and higher clonality rates. Increases in clonality and narrowing of the genetic base over time increased selfing rates and reduced offspring heterozygosity and seedling recruitment. The dynamics of genetic diversity in Bleberan, which was relatively undisturbed, appeared to be highly affected by fluctuations in the number of parental genetic bases (i.e., flowering parents) in each flowering season. Some parents bore flowers in one flowering season but remained in a vegetative state in the following season. This irregularity of flowering individuals caused fluctuations in actual population size, resulting in a different genetic base, mating system, and reproductive outputs in every season. All six loci (i.e., Dia-1, Dia-2, Est-1, Est-2, Est-3, and Skd-1) examined in Bleberan are polymorphic sites, and no missing alleles were noted in any of the observation years. Est-2 was monomorphic in Bejiharjo, where rare and missing alleles were more apparent, particularly at the seedling level. Genetic differentiation over time was observed between Bejiharjo and Bleberan, and increased fragmentation was noted in Bejiharjo. The migration rate between these two landraces also decreased over time. Focusing on maintaining the reproductive and genetic processes of each population by implementing different strategies based on the genetic base, mating systems, and degree of fragmentation and clonality of the landrace is recommended.